Lontar Dharma Pamaculan Implementasi Eko-Religius Masyarakat Agraris Bali - Komang Puteri Yadnya Diari (Pramana: Jurnal Hasil Penelitian, 2021)
Subak in Bali, which has been known internationally until it was designated as a cultural heritage by UNESCO, is a manifestation of the virtue and majesty of Balinese culture. In contrast to the reality, the agricultural tradition has experienced significant degradation, seen from the availability of increasingly eroded land and the limited number of new generations who want to study agriculture. As a functional text, the lontar dharma pamaculan is very important to be used as a reference in the development of agricultural science to prove the truth of traditional knowledge that has existed for a long time. In addition, these efforts can indirectly preserve and maintain the meaning, value and function contained therein. In this study, a qualitative approach with descriptive analytical method was used to determine the implementation of the ecoreligius aspects of Balinese palm-leaf agriculture in Balinese agrarian communities.